Cambridge handbook of project behavior / edited by Lavagnon A. Ika and Jeffrey K. Pinto. - Ika, Lavagnon A.; Pinto, Jeffrey K. (Cambridge University Press, 2025)
Why do projects often deviate from their assigned paths despite careful planning? Leading international scholars in project management research offer invaluable insights into the complex outcomes of projects and the challenges posed by their high complexity and uncertainty. A key resource for practitioners, policymakers, and project professionals.